2020
DOI: 10.1001/jamanetworkopen.2020.23671
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Cardiac Surgeons’ Number of Years in Practice and Surgical Outcomes in New York Cardiac Centers

Abstract: Key Points Question What is the association between cardiac surgeons’ years in practice and operative outcomes on coronary artery bypass grafting (CABG) and valve surgery? Findings In this cross-sectional study of data from early-career (<10 years) and late-career (>10 years) cardiac surgeons practicing between 2014 and 2016 in New York, a lower number of years in practice for cardiac surgeons was significantly associated with a higher risk-adjusted mortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…This relationship between years since training and adoption of certain guideline-recommended interventions has also been observed in other cardiac procedures that are underutilized. 24 While the interplay between surgeon experience, years in practice, and clinical outcomes has been the subject of previous investigation for other types of cardiac surgery, 25,26 the association between surgeon characteristics and adherence to guideline recommendations has been less well studied in cardiovascular surgery. This contrasts with surgical oncology, where hospital and surgeon volume, a surgeon's subspecialty, and the number of years Additional abbreviations as in Figures 1 and 3.…”
Section: Discussionmentioning
confidence: 99%
“…This relationship between years since training and adoption of certain guideline-recommended interventions has also been observed in other cardiac procedures that are underutilized. 24 While the interplay between surgeon experience, years in practice, and clinical outcomes has been the subject of previous investigation for other types of cardiac surgery, 25,26 the association between surgeon characteristics and adherence to guideline recommendations has been less well studied in cardiovascular surgery. This contrasts with surgical oncology, where hospital and surgeon volume, a surgeon's subspecialty, and the number of years Additional abbreviations as in Figures 1 and 3.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] However, surgeon-specific factors, such as age and experience level, have been linked to postoperative outcomes. 16,17 Taken in sum, this suggests that despite the overall impact of the team, there is clearly reason to weight surgeon factors heavily in the consideration of contributors to morbidity. This also necessitates a multipronged approach to improve outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that the implementation of a multidisciplinary cardiac care team improves outcomes and thus the relative impacts of multiple providers cannot be ignored 13–15 . However, surgeon‐specific factors, such as age and experience level, have been linked to postoperative outcomes 16,17 . Taken in sum, this suggests that despite the overall impact of the team, there is clearly reason to weight surgeon factors heavily in the consideration of contributors to morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…This is a valuable independent finding for two reasons. It demonstrates that early‐career surgeons demonstrate competency in CABG surgery, which has been challenged in some studies 12,13 and supported by others 4,14,15 . Second, some articles have discussed whether there should be a maximum age at which surgeons are allowed to practice 16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…Several surgeon‐related factors are known to be associated with surgical outcomes. Surgeon years in practice is one of these factors, with some reports suggesting a concave relationship on complex cases, in which patient outcomes of early‐career surgeons improve for the first number of years in practice, stabilize for the middle of their career, and finally decline for very late‐career surgeons 1–4 . Such findings may suggest the importance of triaging cases of different complexity to surgeons of different experience levels.…”
Section: Introductionmentioning
confidence: 99%